2021
DOI: 10.3390/ijerph18105346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soy Isoflavones on Biochemical Markers of Bone Metabolism in Postmenopausal Women: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: This systematic review and meta-analysis of randomized controlled trials was performed to more completely assess potential changes in bone turnover marker levels in postmenopausal women during the intake of soy isoflavones. PubMed (Medline) and EMBASE were searched for relevant studies, and their quality was evaluated according to Cochrane criteria. The levels of markers were evaluated in a total of 1114 women who ingested mean daily doses of 98.2 mg (30.9 to 300) of soy isoflavones for 3 to 24 months, in comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 94 publications
1
14
0
Order By: Relevance
“…Bone plays an important role in the formation of skeletons as well as blood cells and mineral metabolism in the body. As bone ages, bone minerals decrease and the risk of fracture increases [200]. Osteoporosis is almost always associated with women between the ages of 55 and 70 [201].…”
Section: Promotion Of Osteogenesis and The Prevention Of Osteoporosismentioning
confidence: 99%
“…Bone plays an important role in the formation of skeletons as well as blood cells and mineral metabolism in the body. As bone ages, bone minerals decrease and the risk of fracture increases [200]. Osteoporosis is almost always associated with women between the ages of 55 and 70 [201].…”
Section: Promotion Of Osteogenesis and The Prevention Of Osteoporosismentioning
confidence: 99%
“…Genistein and Daidzein, the component of Isoflavone are able to increase alkaline phosphatase activity in cultured MC3T3-E1 pre-osteoblastic cells and also activate nuclear peroxisome proliferator-activated receptors (PPAR) and mediate the PPAR gene to modulate osteoclast function [15,16]. In addition, Isoflavone can cause a reduction in bone turnover and increased osteoblastic activity through inhibition of both tumor necrosis factor-α (TNF-α) and interleukin-2 (IL- 2), another function is to assist the activation of vitamin D [17,18]. This study is in line with research conducted by Chi et al, where the study involved 40 women for 6 months with 90 mg/day of Isoflavones and caused an increase in a stronger descent of the concentration of ALP and a decrease of IL-6 and TNFα.…”
Section: Discussionmentioning
confidence: 99%
“…Phytoestrogens reduce bone loss during menopause. In a systematic review and meta-analysis of randomized controlled trials, soy isoflavones were found to have beneficial effects on markers of bone formation; however, extensive multicenter studies are required to confirm these findings, as suggested by the authors [110].…”
Section: Experimental and Clinical Studies With Soy Phytoestrogensmentioning
confidence: 95%